ICMER discusses issues in mechanical and automotive engineering - UMP, PNC
Some 100 participants took part in a recent International Conference in Mechanical Engineering Research (ICMER) organized by Faculty of Mechanical Engineering (FKM) and Automotive Engineering Centre (EAC) here recently.